Almendravirus : A Proposed New Genus of Rhabdoviruses Isolated from Mosquitoes in Tropical Regions of the Americas (2017)
Abstract: The Rhabdoviridae is a diverse family of negative-sense single-stranded RNA viruses, many of which infect vertebrate hosts and are transmitted by hematophagous arthropods. Others appear to be arthropod specific, circulating only within arthropod populations. Herein, we report the isolation and characterization of three novel viruses from mosquitoes collected from the Americas. Coot Bay virus was isolated from Anopheles quadrimaculatus mosquitoes collected in the Everglades National Park, Florida; Rio Chico virus was isolated from Anopheles triannulatus mosquitoes collected in Panama; and Balsa virus was isolated from two pools of Culex erraticus mosquitoes collected in Colombia. Sequence analysis indicated that the viruses share a similar genome organization to Arboretum virus and Puerto Almendras virus that had previously been isolated from mosquitoes collected in Peru. Each genome features the five canonical rhabdovirus structural protein genes as well as a gene encoding a class 1A viroporin-like protein (U1) located between the G and L genes (3′-N-P-M-G-U1-L-5′). Phylogenetic analysis of complete L protein sequences indicated that all five viruses cluster in a unique clade that is relatively deeply rooted in the ancestry of animal rhabdoviruses. The failure of all viruses in this clade to grow in newborn mice or vertebrate cells in culture suggests that they may be poorly adapted to replication in vertebrates.